Transcutaneous Electrical Spinal Cord Neuromodulator (TESCoN) Improves Symptoms of Overactive Bladder - Kreydin, Evgeniy; Zhong, Hui; Latack, Kyle; Ye, Shirley; Edgerton, V. Reggie; Gad, Parag (Frontiers in Systems Neuroscience, 2020)
Neuromodulation is a therapeutic technique that is well-established in the treatment of idiopathic Lower urinary tract (LUT) dysfunction such as overactive bladder (OAB). We have recently developed a novel neuromodulation approach, Transcutaneous Electrical Spinal Cord Neuromodulation (TESCoN) and demonstrated its acute effects on LUT dysfunction after spinal cord injury (SCI) during urodynamic studies. We found that TESCoN can promote urinary storage and induce urinary voiding when delivered during urodynamic studies. The objective of this study was to determine whether TESCoN can retrain the spinal neural networks to induce chronic improvement in the LUT, such that positive changes can persist even in the absence of stimulation. In addition, we wished to examine the effect of TESCoN on LUT dysfunction due to multiple pathologies. To achieve this objective, 14 patients [SCI = 5, stroke = 5, multiple sclerosis (MS) = 3, and idiopathic OAB (iOAB) = 1] completed 24 sessions of TESCoN over the course of 8 weeks. Patients completed urodynamic studies before and after undergoing TESCoN therapy. Additionally, each subject completed a voiding diary and the Neurogenic Bladder Symptom Score questionnaire before and after receiving TESCoN therapy. We found that TESCoN led to decreased detrusor overactivity, improved continence, and enhanced LUT sensation across the different pathologies underlying LUT dysfunction. This study serves as a pilot in preparation for a rigorous randomized placebo-controlled trial designed to demonstrate the effect of TESCoN on LUT function in neurogenic and non-neurogenic conditions. New And Noteworthy Non-Surgical modality to reduce incidence of urinary incontinence and improve neurogenic bladder symptom scores (NBSS) in individuals with neurogenic bladder due to spinal cord injury or stroke.